2012
DOI: 10.1080/14498596.2012.733617
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the road edge effect on adjacentEucalyptus grandisforests in KwaZulu-Natal, South Africa, using texture measures and an artificial neural network

Abstract: SPOT-5 multispectral and panchromatic image data were used to compute texture measures to estimate the road edge effect on adjacent Eucalyptus grandis forests. Employing a stepwise selection algorithm enabled the selection of optimal texture measures that were input into a backpropagation artificial neural network. The R 2 of best models ranged from 0.67 to 0.89 for DBH, TH, BA, Volume and LAI on an independent test data set, with a root mean square error (RMSE) range of 0.01-5.36% for the respective variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…This was expected since we employed empirical statistical approaches for deriving the predictive models under two different forest ecosystems. This result is in conformity with other studies that reported different optimal settings for SVM and ANN under different levels and complexities of landscapes [54,68,101,121,122].…”
Section: Support Vector Machines (Svm) and Artificial Neural Networksupporting
confidence: 93%
See 1 more Smart Citation
“…This was expected since we employed empirical statistical approaches for deriving the predictive models under two different forest ecosystems. This result is in conformity with other studies that reported different optimal settings for SVM and ANN under different levels and complexities of landscapes [54,68,101,121,122].…”
Section: Support Vector Machines (Svm) and Artificial Neural Networksupporting
confidence: 93%
“…The networks of road and open paths were used to assist in selecting the endangered tree species by walking in various directions in the intact forest. A handheld LAI-2200 plant canopy analyzer was used to estimate LAI of each sample tree under overcast sky conditions at low solar elevation, i.e., around early morning (8:00-10:00 a.m., Greenwich Mean Time: GMT +2) and late afternoon (3:00-6:00 p.m., GMT +2) with 180˝view restrictor on the sensor [38,68]. To avoid direct sunlight on the sensor, it was required for the operator to take samples of below and above canopy radiation in the opposite direction to the sun.…”
Section: Sampling Procedures and Field Data Collectionmentioning
confidence: 99%
“…However, this statistical technique was criticized for its limitations. For example, Gebreslasie et al [52], Dye et al [88] and Lottering and Mutanga [89] documented that multiple linear regression assumed both linearity and independence between variables, which was seldom observed in forest and remotely sensed data. Furthermore, linear regression also required the absence of collinearity amongst input variables [88,90].…”
Section: Discussionmentioning
confidence: 99%
“…VIF was normally employed to analyze multicollinearity and some variables indicating on collinearity (multicollinearity) might be removed, which resulted in model that explained less variance than the best possible full model with more variables. Therefore, more robust statistical methods, which did not need to make any assumptions about the data, such as artificial Neural Networks (ANN) [89][90][91], Classification and Regression Tree Analysis (CART) [22,92,93], and Random forests (RF) [88,94,95] were widely used to investigate complex relationship between forests stand variables and remotely sensed data. These robust statistical techniques should be given first priority in future remote sensing studies as many researches have already demonstrated that nonlinear interactions might exist between the observed data and remotely sensed data [88,90,96].…”
Section: Discussionmentioning
confidence: 99%
“…Various models of ANN have been used in remote sensing studies such as RBF, back propagation (BP), and multilayer perceptron (MLP) [34], [37], [58], [82]- [84]. The MLP is a commonly used ANN structure that comprises an input layer and an output layer and one or more hidden layers of nonlinearly activating nodes [34], [78], [85].…”
Section: B Ann Classification Algorithm: Multilayer Perceptronmentioning
confidence: 99%